2016
DOI: 10.21890/ijres.16161
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Teachers and ICT: Factors Affecting Pre-service use in School Placements

Abstract: This study examines the factors influencing student teachers" use of information and communication technology (ICT) to teach mathematics. Data collection involved questionnaire surveys and individual follow-up semistructured interviews of student teachers concerning the factors that they felt had hindered or promoted their development in the use of ICT. This study shows that this particular group of student teachers is committed to using ICT in their teaching; they are mostly confident and mostly believe in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…[41] found that it is crucial to improve Indonesia secondary mathematics teachers's on knowledge of ICT and the use of ICT in teaching as they have a largely inadequate knowledge of both aspects. In contrast, [42] found that Turkey pre-service teachers are committed to using ICT in their teaching and they are mostly confident and mostly believe in the value of ICT in developing mathematics teaching competence. However, most of the studies have agreed and concluded that ICT intergration is effective in improving competence of pre-and in-service mathematics teachers, as well as in improving students' performance and achievement.…”
Section: Ict Integration In Developing Teaching Competence Of Pre-service Mathematics Teachersmentioning
confidence: 84%
“…[41] found that it is crucial to improve Indonesia secondary mathematics teachers's on knowledge of ICT and the use of ICT in teaching as they have a largely inadequate knowledge of both aspects. In contrast, [42] found that Turkey pre-service teachers are committed to using ICT in their teaching and they are mostly confident and mostly believe in the value of ICT in developing mathematics teaching competence. However, most of the studies have agreed and concluded that ICT intergration is effective in improving competence of pre-and in-service mathematics teachers, as well as in improving students' performance and achievement.…”
Section: Ict Integration In Developing Teaching Competence Of Pre-service Mathematics Teachersmentioning
confidence: 84%
“…As technology takes an increasing role in knowledge acquisition and content assimilation and understanding, there is a pressing need to situate the technological competence of teachers, and thus their ability to meet the emerging learning styles of digital natives. Numerous research studies (Aslan & Zhu, 2016;Bozkurt, 2016;Zelkowski et al, 2013) have focused on pre-service teachers, but it is even more crucial to look at the critical mass of practicing teachers and unveil factors that hinder or facilitate this technological uptake. Somelch (2008) reported minimal pedagogical change, and Aslan and Zhu (2016) referred to low-level use, whereby only basic procedures like Internet information search, presentation programs and other application programs, supplement teaching practices.…”
Section: Introductionmentioning
confidence: 99%
“…The results show, however, that supportive behaviors alone are not enough. This was seen in the analysis of [30]. Most teachers believed that technology would make students more inspired, love mathematics, gain more insight, and deal with challenges in the real world.…”
Section: Conceptual Frameworkmentioning
confidence: 99%